2021
DOI: 10.1038/s41598-021-87923-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of climate change on the Pleistocene rock art of Sulawesi

Abstract: The equatorial tropics house some of the earliest rock art yet known, and it is weathering at an alarming rate. Here we present evidence for haloclasty (salt crystallisation) from Pleistocene-aged rock art panels at 11 sites in the Maros-Pangkep limestone karsts of southern Sulawesi. We show how quickly rock art panels have degraded in recent decades, contending that climate-catalysed salt efflorescence is responsible for increasing exfoliation of the limestone cave surfaces that house the ~ 45 to 20-thousand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 46 publications
(83 reference statements)
2
27
0
Order By: Relevance
“…Damaged red ochre hand stencils adorn the walls of LBB, likely produced during the Pleistocene (Aubert et al., 2014), and Late Holocene charcoal drawings (Huntley et al., 2021). Undated child‐sized hand stencils and comb‐like “narrow‐finger” stencils (a regionally unique style of Pleistocene antiquity; Aubert et al., 2014; Oktaviana et al., 2016) were observed in a small, difficult‐to‐access hollow that is suspended above the main shelter at LBB (YLP pers.…”
Section: The Lbb Excavationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Damaged red ochre hand stencils adorn the walls of LBB, likely produced during the Pleistocene (Aubert et al., 2014), and Late Holocene charcoal drawings (Huntley et al., 2021). Undated child‐sized hand stencils and comb‐like “narrow‐finger” stencils (a regionally unique style of Pleistocene antiquity; Aubert et al., 2014; Oktaviana et al., 2016) were observed in a small, difficult‐to‐access hollow that is suspended above the main shelter at LBB (YLP pers.…”
Section: The Lbb Excavationsmentioning
confidence: 99%
“…The technically‐sophisticated Upper Industry macroblades – in combination with evidence for parietal art (Huntley et al., 2021, p. 7), portable art (Brumm et al., 2020; Langley et al., 2020), beads, and bone tool technology (Brumm et al., 2017) – highlight the complex technological and social relations between groups at this early period. Symbolism specifically related to stone flaking or tool use during the Upper Industry is suggested by five stone artefacts with geometric engravings on the cortex from the Upper Industry at LBB (Brumm et al., 2017, 2020).…”
Section: Upper Industry At Lbbmentioning
confidence: 99%
“…More recently, Maros made headlines again in the archeological world when the dating of several cave paintings revealed ages of up to 45,000 years, leading them to become the oldest rock art in the world [11,12]. Many caves of the Maros karst harbor Pleistocene parietal art, rivaling the 'ice age' cave art of western Europe [13].…”
Section: Archeologymentioning
confidence: 99%
“…Even when the habitat is not destroyed itself, noise and dust linked to quarrying are known to disturb swiftlets, bats, and bat colonies, which are the main food providers for obligate cave fauna and the only one for guanobionts, but we also lack information on the distribution of swiftlets and bats in this part of the karst. They are also, together with climate change, the greatest threat on the preservation of the invaluable prehistoric rock art of the Maros karst [13] as well the main cause of the current disfiguration of the unique landscape of the karst outside of the National Park boundaries.…”
Section: Conservation Issuesmentioning
confidence: 99%
“…A recent study demonstrated that salt efflorescence is the underlying cause of exfoliation of the case-hardened limestone surfaces that form the substrate for the older Pleistocene paintings 15 . Case-hardening is produced by the precipitation of solutes at the limestone’s surface to form a durable crust.…”
Section: Introductionmentioning
confidence: 99%